REVITALISASI MUTU PENDIDIKAN DI WILAYAH 3T - Penni Rira; Riska Reti Sinding (JIP: Jurnal Ilmu Pendidikan, 2023)
The aims of this research are 1) to find out the nature or meaning of the 3T area, 2) to find out indicators of low quality education in the 3T area, 3) and to find out the strategy for improving the quality of education in the 3T area along with the improvement procedures. By using the qualitative research method of literature study, namely by collecting information from various reading books and literature, it was found that education in the 3T areas or frontier, remote, and underdeveloped areas is currently still low. This condition is caused by various things, one of which is Indonesia's topography which is spread from east to west. An area is said to be a 3T region regulated in the Republic of Indonesia Presidential Regulation Number 131 of 2015 concerning underdeveloped areas, one of which is the low quality of education. Therefore it is necessary to improve the quality of education so that educational goals can be realized optimally. Efforts to increase this are not only carried out by one party, but by all parties, namely from the center, educational units, to the community.